근관절건강학회지 게재 논문 분석: 2008년부터 2020년까지 - 박미성(Park, Mi-Sung); 이경숙(Lee, Kyung-Sook); 신계영(Shin, Gyeyoung); 우수희(Woo, Soo-Hee); 임경춘(Lim, Kyung-Choon); 최희정(Choi, Heejung); 진수지(Jin, Soo-Ji); 박연환(Park, Yeon-Hwan) (근관절건강학회지, 2022)
Purpose: To identify research trends in the Journal of Muscle and Joint Health. Methods: In total, 315 studies published between 2008 and 2020 in the Journal of Muscle and Joint Health were reviewed using analysis criteria developed by the authors Results: Most participants were adults or older adults, they mostly had arthritis. The types of research design were descriptive research (46.4%), quasi-experimental design (21.9%), randomized controlled trial (1.9%), and qualitative research (4.1%). The occupation of most authors was professor in universities (61.0%). Data were collected mostly in hospitals (41.6%) or communities (24.4%) using a questionnaire (52.4%). Written consent was obtained at 75.6% and 47.9% of studies were approved by the Institutional Review Board (IRB). The instruments measuring physical concepts such as pain, flexibility, sense of balance and fatigue were mostly used. The most common interventions in experimental studies were physical interventions, with the main being exercise. Key words were categorized into four nursing meta-paradigms: human, health, environment and nursing. The most frequently reported key words were included in the health domain. The most frequently used key words were physical intervention, older patient, osteoarthritis, pain and depression. Conclusion: The results suggest that more research studies targeting various age groups related to muscle and joint health are required. Additionally there is a need to increase the number of qualitative studies, randomized experimental studies, and systematic review studies. It is necessary to pay attention to compliance with research ethics publication regulations.